Sustainability Factors Influencing Industrialised Building System (LBS) Prospects For Post-Disaster Building Reconstruction From Productivity And Quality Aspects - Mohd Yusri, Yushani Syafrina (Universiti Sains Malaysia, 2018)
The Construction Industry Master Plan (2006–2015) is intended to address sustainability in the Malaysian construction industry with the objective of globalising its market. As the sustainability awareness rises globally, the construction industry is under pressure to improve its efficiency. The adoption of Industrialised Building Systems (IBS), for which its components are built off-site, has the potential of promoting sustainability development. However, there is high competitive between IBS method and conventional method since IBS is a new method of construction. IBS system comes with its own advantages and specialty in construction industry which is better control of production environment, minimizing construction waste, using efficient building material energy, and stabilising work conditions. This research focuses on projects that use IBS system a method of construction. This project aims to determine the hierarchy sustainability factors into different productivity and quality aspects. There are four (4) sustainability factors that had been categorized which are environment, economy, social and technology. Each of the sustainability factors has their effects on productivity and quality aspects that influence to building reconstruction after a disaster. End of this research, the highest of hierarchy for productivity aspect is the environment factors while the highest hierarchy for quality factors is technology. Throughout this project, further research on sustainability factors should be conducted to promote IBS adoption on productivity and quality aspect.